Intrathoracic splenosis – lesson learned: a case report. Issue 1 (December 2016) - Tulinský, Lubomír; Ihnát, Peter; Mitták, Marcel; Guňková, Petra; Zonča, Pavel
Abstract Background Intrathoracic splenosis presents an extremely rare thoracic lesion occurring after a simultaneous rupture of the spleen and diaphragm as a consequence of heterotopic autotransplantation and implantation of splenic tissue. Intrathoracic splenosis is usually an asymptomatic, incidental finding, which should be ideally managed without surgical intervention. Case presentation We present a case of 68-year old woman with intrathoracic splenosis. Patient presented with a 2-month history of a dry cough unresponsive to administered antibiotics and antimycotics. Computed tomography (CT) of the chest revealed two homogeneous pleural nodules (diameters of 2 and 4 cm) in the left upper lung field. Two consequent CT-assisted transthoracic core-cut biopsies were performed. Histopathology examination of both biopsy specimens was inconclusive (haemorrhagic and non-specific tissue). After that, patient was referred to the department of thoracic surgery with a suspicion of malignant mesothelioma or metastatic lesions. Thoracoscopic revision of the left pleural cavity was performed and the presence of pleural nodules was confirmed. Bloody looking nodules were resected (standard thoracoscopic resection). Postoperative recovery was uneventful. The histopathology examination of the specimen showed normal splenic tissue. Only with the histopathology report in hand, a detailed medical history was taken. It revealed a gunshot injury requiring splenectomy (without known diaphragm or lung injury) 44 years ago (one of the longest time periods in the literature). Conclusions We would like to point out that following the recommendations regarding splenosis may be very difficult in daily routine practice. The simple question regarding abdominal trauma in a patient's history can lead the clinician to the diagnosis of splenosis, which can be unequivocally established via scintigraphy. The importance of thorough medical history taking, therefore, cannot be underestimated.